A study to evaluate the outcome following Anderson Hynes pyeloplasty in hydronephrosis patients with cummings stent and D-J stent - Mukherjee, Ramanuj; Mullick, Mitrajit; Samanta, Sudipta (International Journal of Research in Medical Sciences, 2018)
Background: Uretero-Pelvic Junction Obstruction (UPJO) is an important cause of hydronephrosis in pediatric age group. The choice of treatment could be conservative or surgical. Commonly Anderson-Hynes pyeloplasty is practiced with internal, external or partly internal partly external stent. Methods: This was a prospective study of 40 patients with UPJO, divided into 2 groups consecutively, each consisting of 20 patients. All patients underwent open Anderson-Hynes pyeloplasty. Cummings stent were given in one group for drainage and conventional DJ stent were used for another group. Results: The mean hospital stay was lesser in DJ stent group (8.4±2.13) compared to Cummings stent group (11.4±0.68), not only in respect to primary admission, but also including readmission for cystoscopic stent removal. The incidence of complications was also fewer in Cumming stent group. Stent migration and urinary tract infection (UTI) were more associated with DJ stent (2 each) than Cumming stent (0 each). However, dysuria was more in case of cumming stent (2 patients) than DJ stent (1 patient). Conclusions: The mean hospital stay in DJ stent insertion is less even if duration for cystoscopic removal is considered. The complication of stent removal and UTI are more with DJ stent though dysuria is more in case of Cummings stent.